(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
This article is devoted to the study of the factors of competitiveness of radio advertising in modern conditions. In the context of the transformation of the advertising market, the psychological features of radio advertising are revealed and considered as the advantages of radio advertising. The features of the frequency of advertising contacts at the radio station are determined. The genres of radio advertising are considered as a way to rebuild from competitors for advertisers as an advantage of advertising on the radio